Wind turbine tower collapse due to flange failure: FEM and DOE analyses. (October 2019) - Alonso-Martinez, Mar; Adam, José M.; Alvarez-Rabanal, Felipe P.; del Coz Díaz, Juan J.
Abstract: Although a large number of papers have been published to date on failures in wind turbines, most of them have focused on blade failures and less attention has been paid to the tower failures. This paper analyses the causes that led to the failure of one element that finally caused the whole tower to collapse. A diagnosis of the cause of the failure was carried out after an initial on-site inspection, when the origin of the failure appeared to be in the flange that joined the tower to its base. An experimental program was carried out to analyze the characteristics of the steel in the area nearest to the flange. A non-linear simulation was then performed by the finite element method (FEM) of the flange area where the failure had occurred, including the bolts, their prestressing forces and the contact between the joined surfaces. In order to study the influence of different variables on the flange's structural response, a method based on the Design of Experiments (DOE) was used on the FEM model. Finally, the main lessons learnt from the experience are given with the aim of contributing to improving the design and construction of wind turbine towers. Graphical abstract: Unlabelled Image Highlights: Wind tower collapse due to the failure of a flange is analyzed. Analysis of the material properties is needed to identify the causes of the failure. Finite Element model shows the load distribution in the broken section. The most influential parameters are obtained applying Design of Experiments (DOE).